The Ten Percent Solution - Wheatley, Bronwen (Canadian Perspectives on Academic Integrity, 2021)
The Fall 2020 semester for the University of Calgary's general chemistry course CHEM 201 was completely different from the previous year's Fall semester: student enrolment had increased, the number of lecture sections offered had decreased, and the course's lectures, labs, and tutorials were all held online. Planning for CHEM 201 during the summer of 2020 was therefore a completely new experience and the main concerns were the feasibility and accessibility of coursework, and the ever-present concern that the new online format would allow or even encourage students to engage in academic misconduct. Reflections about preparing for and offering an introductory science course (CHEM 201) to 800 students in an online setting will be presented and the efforts to make academic integrity part of the course design will also be discussed. In particular, a 10% final exam had an unexpected effect on the structure, management, and delivery of the course.